Faktor-faktor yang Mempengaruhi Unmeet Need KB pada PUS: Literature Review - Cahyani, Sahda Mutiara; Sutrisminah, Emi; Machfudloh, Machfudloh (Jurnal Kebidanan Malakbi, 2025)
One indicator of declining population development in Indonesia is the decline in the number of unmet needs. The proportion of women who do not currently use any kind of contraception and do not wish to have more children or postpone getting pregnant is known as unmet need. In Indonesia, there was an increase of 9.1% in 2016 and the incidence of unmet needs was 8.5 percent in 2017. This The goal of the study is to determine the variables that affect PUS's unmet family planning needs. The method used is a literature review study which includes a systematic search study of computerized databases: Scopus, ProQuest, PubMed, Garuda, Science Direct, and Google Scholar in the form of research articles totaling 11 articles published from 2019-2022, full text, speak Indonesian and English in accordance with the inclusion criteria. Article searches used the keywords "unmet need", "contracepcion", "unmet need factors", "unmet need for contraception", "family planning", "unmet need factors in mothers who are not family planning acceptors". The results of the study show that the factors that influence the unmet need for family planning in PUS are: Knowledge (p value= 0.033), age (p value = 0.077), employment (p value= 0.004), education (p value= 0.004), history of family planning (p value= 0.00), parity (p value= 0.01), place of residence (p value= 0.01), husband's support (p value= 0.03). Factors that influence unmet need for EFA are knowledge, age, employment, education, history of family planning, parity, place of residence, and husband's support. . Health workers are expected to work together with KB cadres and Village PLKB to disseminate in-depth information about the KB program so that it can reduce cases of unmet need. Fertile couples who have not used KB are expected to seek information through existing health workers.